A Playful Approach to Fostering Motivation in a Distance Education Computer Programming Course: Behaviour Change and Student Perceptions - Pilkington, Colin (International Review of Research in Open and Distributed Learning, 2018)
The central role of motivation to learn in distance education has been noted, and gamification has been proposed as one approach to promote student motivation. This study explores promoting motivation in a distance education, third-year computer programming course via a gamified approach to improve coursework participation and student experience. Motivation was examined from a Self-Determination Theory (SDT) perspective, as gamified approaches often rely on external motivation and the explicit use of competition to engender internal motivation leading to desired behaviours. The results of using gamification in education are mixed, and its use is controversial. Two cycles of action research on the introduction of eight playful elements are reported on, and data relating to student engagement with the course and a student questionnaire was gathered. There was little evidence that the intervention led to behaviour change or improved scores; however, students responded very positively to the intervention, although some negative themes emerged. The extent to which the playful approach supported the basic psychological needs of SDT is discussed and the intervention’s results critically considered, including whether the effort involved in such an approach was worth it. It was concluded that such playful approaches might have positive motivational effects.